1A.002 Factors associated with participant attrition in an app-based unintentional child injury intervention. (14th March 2021) - Li, Jie; Ning, Peishan; Cheng, Peixia; Schwebel, David; Yang, Yang; Wei, Xiang; He, n Jieyi; Wang, Wanhui; Li, Ruotong; Morgan, Casie; Hu, Guoqing
Abstract : Background: High attrition rates threaten evaluation of the effectiveness of mobile health interventions. We explored the factors associated with attrition of study participants in an app-based clinical trial. Methods: This six-month cluster randomized control trial (RCT) implemented two app-based interventions: an unintentional child injury prevention app in the intervention group (Bao Hu San) and a nutrition app in the control group. The study included 2, 920 caregivers of 3–6 year-old preschoolers in Changsha, China. Follow-up surveys were conducted 3 and 6 months after baseline, and data on app engagement was collected electronically during the RCT. Associations within intervention and control groups were tested and quantified separately using adjusted odds ratio (aOR) based on logistic regression models. Results: The six-month attrition rate was 32.2%. Attrition rates differed significantly between control and intervention groups (35.7% vs. 28.9%, p<0.01). For the intervention group, aORs of attrition risks were 1.43 for females; 1.59 and 1.41 for caregivers within 2 younger age groups; 1.67 for lower-educated individuals; and 2.80 for those who learned less during participation, respectively. For the control group, aORs of attrition risks were 1.69 for those with lower login frequency; 2.18 and 1.84 for those who learned least and less; and 2.51 for those with shorter learning duration. Conclusions: Demographic characteristics and app engagement were associated with attrition. Learning Outcomes: Researchers and practitioners should consider demographic factors and engagement when designing app-based interventions.